Perlindungan Hukum Pidana oleh Sekolah dalam Mengatasi Perundungan yang Dilakukan Siswa (Studi Kasus di SMP Yogyakarta) - Ananda Salsabilla Styaningrum; Fuadi Isnawan (Fakultas Hukum Universitas Islam Indonesia, 2024)
Bullying is not a new phenomenon; even today, it frequently occurs in both societal and school environments. Bullying encompasses not only physical violence but also verbal and psychological abuse. The aim of this research is to explore the objective conditions of legal protection for bullying victims in junior high schools in the Yogyakarta region. The research questions are: How does the school provide legal protection for bullying victims? What are the obstacles faced by schools in offering legal protection to children who are victims of verbal and physical bullying? This research is classified as empirical legal research, employing both sociological and normative approaches. This data was collected through literature review and field studies, including interviews with relevant sources. The results of this study produce data that forms of bullying can be categorized into three types: physical, verbal, and psychological. The legal protection that schools can offer to bullying victims includes preventive measures such as prevention, and responsive measures involving consequences, punishments, or sanctions.